Merancang Panel Kontrol Untuk Pompa Air dan Motor Pengerak Solar Cell - Herisajani herisajani; Nasrul nasrul; Yandrika Putra (Elektron : Jurnal Ilmiah, 2014)
At this present time increasing electrical energy requirements, and therefore found the latest energy is solar energy. Solar energy can be harnessed as a potential alternative energy source because the energy is very large as well as environmentally friendly. Tool that can be used to convert sunlight directly into electricity is called photovoltaic. On the control panel to control the water pump on the motor control circuit design life turns automatically and manually. To control the timing of the displacement of the pump used to pump two timers. On the control panel of diesel propulsion sell used four times the displacement step. Switching time between steps in the set by a timer. The control panel uses the same circuit with the motor circuit alternating rounds.